Analysis of Administrative Penalty for Late Issuing Tax Invoices in Indonesia: A Comparative Study from Vietnam - Khodijah, Siti; Rosdiana, Haula (Politeknik Ganesha Medan, 2024)
This study analyzes and compares the administrative penalty for late issuing tax invoices between Indonesia and Vietnam. The existence of a penalty has not been a driving factor for taxpayers to fulfill their tax obligations. Article 14 paragraph (4) General Provisions and Tax Procedures Law regulates the tax penalty for late issuing tax invoices, the same as for those who do not issue invoices. The administrative penalty needs to be analyzed more and compared with other countries' practices. VAT penalty cannot necessarily increase the compliance of taxable entrepreneurs. This research uses primary and secondary data sources for the qualitative method. The results of this study indicate that tax penalties should be designed by looking at the level of taxpayer error. Vietnam has no administrative penalty for the late issue of tax invoices but differentiates more penalties for tax invoices according to the level of violation. Tax penalties in Indonesia should be designed by considering the level of taxpayer violation, as Vietnam regulates. Administrative penalties for late tax invoices should not be the same as those imposed on taxpayers who did not issue tax invoices. The study recommends that tax authorities re-design the administrative penalties policy regarding tax invoice violations.